Building Security Operations Center (SOC) using open source technologies SIEM for industries - Rabby, Zahidul Haque (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.